МАРКАЗИЙ ОСИЁ СИЁСИЙ ЎЗГАРИШЛАР ДАВРИДА - Ҳайдаралиев, Ш. (FAN va JAMIYAT, 2021)
This article reflects the new foreign and good-neighborliness policy in the spirit of mutual trust that is emerging in Central Asia today. The policy of political equality, stability and good neighborliness, proposed under the leadership of President Sh.M.Mirziyoyev, is held not only from the point of view of Central Asia, but also taking into account the interests of the entire region. The foreign policy of New Uzbekistan is developing with new proposals and initiatives, offering the world community methods of political dialogue.